Predictors of quality of childcare centers in low-income settings: findings from a cross-sectional study in two Nairobi slums - Nampijja, Margaret; Langat, Nelson; Oloo, Linda; Okelo, Kenneth; Muendo, Ruth; Kiyeng, Martin; Amboka, Patrick; Abboah-Offei, Mary; Ray, Anna; Kitsao-Wekulo, Patricia; Kimani-Murage, Elizabeth W.; Elsey, Helen (Frontiers in Public Health, 2023)
Background Rapid urbanization and increased women’s involvement in paid work have contributed to the upsurge of informal childcare centers, especially in low-income settings where quality is a major issue. However, there are limited data on the factors associated with the quality of childcare centers in informal settlements in Africa. Methods We conducted a quantitative observation and questionnaire survey of 66 childcare centers to identify the factors associated with the quality of childcare services in two informal settlements (Korogocho and Viwandani) in Nairobi. The quality of the centers (outcome variable) was assessed using a locally developed tool. Data on center characteristics including type, size, location, length of operation, charges, and number of staff were collected. Center providers’ knowledge, attitude, and practices (KAP) in childcare were assessed through a questionnaire, focusing on nurturing care and business management. Data were described using means and standard deviation or frequencies and percentages. Associations between quality center score (outcome variable) and other variables were examined using multivariable linear regression to identify potential predictors of the quality of the center environment. Findings A total of 129 childcare centers were identified and categorized as home-based (n = 45), center-based (n = 14), school-based (n = 61), and church-based (n = 9). The number of home-based centers was particularly high in Viwandani (n = 40; 52%). Only 9% of home-based centers reported any external support and 20% had any training on early childhood development. Of the 129 centers, 66 had complete detailed assessment of predictors of quality reported here. Unadjusted linear regressions revealed associations between quality of childcare center and center providers’ education level, type of center, support received, caregiver–child ratio, number of children in the center, and center providers’ KAP score (p < 0.05). However, in the multivariable regression, only higher levels of center provider KAP (β = 0.51; 95% CI: 0.18, 0.84; p = 0.003) and center type (β = 8.68; 95% CI: 2.32, 15.04; p = 0.008) were significantly associated with center quality score. Implication Our results show that center providers’ knowledge and practices are a major driver of the quality of childcare centers in informal settlements in Nairobi. Interventions for improving the quality of childcare services in such settings should invest in equipping center providers with the necessary knowledge and skills through training and supportive supervision.